"One of the Two Good Outcomes": Turning Defeats into Victories in the Islamic State's Flagship Magazine Rumiyah. Issue 8 (16th November 2020) - Lakomy, Miron
ABSTRACT: This paper attempts to understand the most evident propaganda methods and leading themes exploited in the recent issues of the Islamic State's flagship Anglophone magazine Rumiyah to downplay its increasingly visible crisis. It argues that there are several leading methods of damage control utilized by Daesh. To begin with, a noticeable effort has been made to recover the "winner's image" of the Islamic State with the use of card-stacking propaganda devices. This has been combined with the widespread promotion of martyrdom as an end-goal for all mujahidin, which is symbolized by the slogan: "one of the two good outcomes." Finally, the crisis of the group has also been downplayed by a plethora of religion-related manipulation techniques and name-calling propaganda devices, utilized predominantly to exploit sectarian tensions.